2014
DOI: 10.5897/ajar2013.7237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies on transmission of mung bean yellow mosaic virus (MYMV) by Bemisia tabaci Genn. in Mungbean

Abstract: The whitefly Bemisia tabaci Genn. is an important pest worldwide because of its ability to cause damage by direct feeding and its role as a vector of plant viruses including geminiviruses. Yellow mosaic virus (MYV) is a serious disease of pulse crops including mungbean, blackgram, frenchbean, pigeonpea and soybean. Yellow mosaic diseases are one of the most important viral diseases in mungbean caused by mungbean yellow mosaic virus (MYMV) which lead to severe yield reduction and it necessitates development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Whitefly is an extremely efficient vector as even a single viruliferous adult can transmit the YMV within 24 h of AAP and IAP (Malathi and John, 2009). Govindan et al (2014) reported 10 viruliferous adult whiteflies after 24 h each of AAP and IAP causing YMD with 70.50% virus transmission efficiency, while 20 viruliferous whitefly adults after 48 h of AAP and 24 h of IAP has resulted in 85% virus transmission efficiency. Since YMD can be very effectively spread by very low densities of adult whiteflies; therefore, no correlation could be established between the number of whiteflies and YMD severity (Akhtar et al, 2011).…”
Section: Screening Using Viruliferous Whitefliesmentioning
confidence: 99%
“…Whitefly is an extremely efficient vector as even a single viruliferous adult can transmit the YMV within 24 h of AAP and IAP (Malathi and John, 2009). Govindan et al (2014) reported 10 viruliferous adult whiteflies after 24 h each of AAP and IAP causing YMD with 70.50% virus transmission efficiency, while 20 viruliferous whitefly adults after 48 h of AAP and 24 h of IAP has resulted in 85% virus transmission efficiency. Since YMD can be very effectively spread by very low densities of adult whiteflies; therefore, no correlation could be established between the number of whiteflies and YMD severity (Akhtar et al, 2011).…”
Section: Screening Using Viruliferous Whitefliesmentioning
confidence: 99%